Determinants of E-wallet Acceptance Among Low-Income Group in Malaysia: a Pilot Study - Syafatul Aqilla Binti Samar, Nur; Ismail, Shafinar; Abd Rahman, Nur Hayati (IKONOMIKA, 2025)
Developing acceptance of e-wallets among low-income groups is challenging due to factors such as financial limitations, digital literacy gaps, and concerns about security and usability. This study proposes a relationship model using a quantitative research design to validate the hypothesized factors and establish their interconnections. The key determinants influencing e-wallet acceptance include performance expectancy, effort expectancy, and facilitating conditions, with behavioral intention serving as a mediating factor. To ensure the reliability and validity of the research instrument, a two-step verification process was conducted. First, a panel of experts reviewed the questionnaire during the validation phase, and their feedback was incorporated. Second, a pilot study was conducted to examine the instrument's consistency using Cronbach’s Alpha coefficient reliability screening in SPSS 29 software. The results confirmed that all items were reliable, with a Cronbach’s Alpha coefficient exceeding 0.7, indicating strong internal consistency